Populism and democracy in Costa Rica: analysis of the inter-branch conflict in 2025 (Revista Rupturas, 2026)
Since the dawn of the 21st century, Costa Rican democracy has faced new challenges that have reshaped the national political landscape, such as the crisis of the political party system, electoral dealignment, and declining citizen participation at the polls. This research, however, aims to highlight new challenges that go beyond the merely electoral: the rise of anti-democratic, anti-system, and anti-institutional discourses promulgated from the highest echelons of political power, with systematic attacks on the legitimacy of public institutions and the representative democratic system. In this sense, it is argued that there is a growing trend toward democratic deterioration in the country, which is being exacerbated by new populist attitudes that challenge Costa Rica's historic democratic achievements.
Keywords: democracy; inter-branch conflicts; populism; democratic institutionality; human rights